THE INFLUENCE OF TEACHERS’ WORK MOTIVATION AND PRINCIPALS’ MANAGERIAL COMPETENCE ON TEACHERS’ PERFORMANCE - Hamdani Hamdani; Nila Kesumawati; Muhammad Kristiawan (Sriwijaya University Learning and Education International Conference, 2018)
This study aimed at determining the effect of work motivation and principal managerial competence on teachers’ performance. This research used descriptive quantitative. The populations of the research were 150 teachers as State High School in Banyuasin. The samples were 60 teachers. Sampling technique in this research was Proportionate Stratified Random Sampling. The instruments were nquestionnaires. Data were analyzed using correlation and multiple regressions. The results showed that 1) teachers’ work motivation influences the teachers’ performance in SMA Banyuasin with 89,3%; 2) the principal’s managerial competence influences teachers’ performance in SMA Banyuasin with 76,6%; and 3) teachers’ work motivation and principal’s managerial competence influence teachers’ performance in SMA Banyuasin with 89,3%.